JUDICIAL SCRUTINY IN THE RULING OF THE KUHAP - Ahwan, Ahwan; Ristanti, Yuni (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
The Draft Criminal Procedure Code of 2025 "reverts" to using the institution of Pretrial as an instrument that implements the function of judicial scrutiny. Previously, the values of accountability were realized in the institution of Commissioner Judges and Preliminary Examining Judges. The institution of pretrial itself has been criticized from both normative and implementation aspects in the 1981 Criminal Procedure Code. This article aims to analyze the formulation of pre-trial in the Draft Criminal Procedure Code 2025. By using doctrinal research, this article argues that the pretrial formulation in the Draft Criminal Procedure Code 2025 has not comprehensively implemented the values of accountability as the crystallization of the principle of judicial scrutiny. Despite some progressive provisions, normatively, the Bill characterizes pretrial as an institution that acts post-factum and is limited to administrative functions. The formulation of pretrial still maintains a reactive function where its work is based solely on requests. In addition, the scope of pretrial proceedings formulated in the definition tends to be degraded by subsequent operational articles.